2017
DOI: 10.22587/ajbas.2017.11.16.10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trematode Larval Infections in Some Red Sea Snails

Abstract: Marine snails play an important role in the transmission of cercariae to fish as a source of zoonotic diseases. In Saudi Arabia, studies on parasitic infections in marine snails are rare. In the current study, a total of 550 marine snails belonging to the genus, Nerita were collected randomly from Obhor bay, Red Sea at Jeddah city, Saudi Arabia. Snails were collected monthly at the period from January to December 2016. They were exposed to light and crushed to assess the presence of larval trematodes. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Crepidula fornicata had the highest prevalence of turbellarians during the summer months, followed by autumn. Several studies have found the highest prevalence of turbellarian infections to occur during the summer and autumn months in species such as the Mediterranean mussel Mytilus galloprovincialis and Red sea snails Nerita spp (Crespo-González et al, 2010;Hassan et al, 2017;Bhaby, 2018). Some suggest that turbellarians leave their hosts when the environmental temperature drops, causing lower intensities during colder mouths (Fleming, 1986;Crespo-González et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Crepidula fornicata had the highest prevalence of turbellarians during the summer months, followed by autumn. Several studies have found the highest prevalence of turbellarian infections to occur during the summer and autumn months in species such as the Mediterranean mussel Mytilus galloprovincialis and Red sea snails Nerita spp (Crespo-González et al, 2010;Hassan et al, 2017;Bhaby, 2018). Some suggest that turbellarians leave their hosts when the environmental temperature drops, causing lower intensities during colder mouths (Fleming, 1986;Crespo-González et al, 2010).…”
Section: Discussionmentioning
confidence: 99%